School Education in the Draft National Education Policy 2019: A Preliminary Review - Ramachandran, Vimala (Voices of Teachers and Teacher Educators, 2019)
This article is focussing on some specific aspects of school education, ECCE and teacher education of draft NEP 2019. It in turn tried to flag certain issues of learning gaps, conducting repeated assessments as a solution for that and expressed the need for decentralisation. The article also appreciates the importance placed on pre school education. Further the author expresses an urgent need to develop a comprehensive teacher management policy.